Oil, international payments and reform / by S.L.N. Simhan and D.Hemalatha - Simha, S.L.N.; D.Hemalatha (Madras, 1975)
Far-reaching developments are taking place in the sphere of inter national finance and the sharp hike in the price of oil has intro duced an extraordinary element into the picture of vast politico economic significance. The lite rature on these developments is vast and varied, much of which is not easily available to the Indian public. What the authors have done is to present the rich and complex material in a compact form, with a historical account and a lucid and integrated ana lysis of the many facets of the problem of world payments and reform. The oil and energy situa tion in India and prospects are dealt with in some detail. Toge ther with 46 very comprehensive and up-to-date statistical tables and some appendices on inter national monetary co-operation and reform, the publication should prove to be an invaluable reference volume to readers in India and abroad, as there are few publi cations of this comprehensiveness. A unique book, of immense inte rest to scholars and the general public alike.
Keywords: Offields production method